Child abuse and the role of a dentist in its identification, prevention and protection: A literature review - Vishwendra Singh; Gurvanit Lehl (Wolters Kluwer Medknow Publications, 2020)
Child abuse, a reprehensible act, pervades all strata of society. Dentists are more likely to encounter such cases in their daily practice. However, such cases usually go unreported due to lack of adequate knowledge. Practitioners flinch from reporting these due to various reasons, and this sets up a vicious cycle which traps the victim leading to grave long-term consequences. This review aims to collect all literature available on PubMed, PubMed Central, MEDLINE, Google Scholar, and Google search engines on the role of dentists in child abuse identification and information and summarize these details. The review will shed light on the identification of abuse in dental settings, the various legal recourses and organizations related to it, and how dentists can better equip themselves to tackle such cases if they come across one. The review also makes certain recommendations by which dentists and healthcare providers in general can better prepare themselves for such contingencies.